2002
DOI: 10.1063/1.1507824
|View full text |Cite
|
Sign up to set email alerts
|

The embedding of the space–time in five dimensions: An extension of the Campbell–Magaard theorem

Abstract: We extend Campbell-Magaard embedding theorem by proving that any ndimensional semi-Riemannian manifold can be locally embedded in an (n+1)dimensional Einstein space. We work out some examples of application of the theorem and discuss its relevance in the context of modern higher-dimensional spacetime theories.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
76
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(78 citation statements)
references
References 9 publications
(9 reference statements)
0
76
0
2
Order By: Relevance
“…It is interesting to have a look at the components of the extrinsic curvature tensor Ω αβ of the hypersurface ψ = const of M 5 . In the coordinates of (5) it can easily be shown that Ω αβ is given by Ω αβ = − 1 2k ∂g αβ ∂ψ [18], so that the nonvanishing components of Ω αβ are…”
Section: The Embedding Of Gödel's Universe In Five Dimensionsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is interesting to have a look at the components of the extrinsic curvature tensor Ω αβ of the hypersurface ψ = const of M 5 . In the coordinates of (5) it can easily be shown that Ω αβ is given by Ω αβ = − 1 2k ∂g αβ ∂ψ [18], so that the nonvanishing components of Ω αβ are…”
Section: The Embedding Of Gödel's Universe In Five Dimensionsmentioning
confidence: 99%
“…with ε 2 = 1, represents the line element of M n+1 in a coordinate neighbourhood V of M n+1 [6,26]. In the light of the above theorem let us take n = 4, ε = 1, φ = −k 2 , where k is a constant, and the set of analytical functions {g αβ (t, x, y, z, ψ} 2w(x + kψ)) = 0.…”
Section: The Embedding Of Gödel's Universe In Five Dimensionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The theory that motivates such scenario is the Induced Matter Theory (IMT) [11,12]. In this theory inflation can be recovered from the Campbell-Magaard theorem [13][14][15][16][17], which serves as a ladder to go between manifolds whose dimensionality differs by one. This theorem, which is valid in any number of dimensions, implies that every solution of the 4D Einstein equations with arbitrary energy momentum tensor can be embedded, at least locally, in a solution of the 5D Einstein field equations in vacuum.…”
Section: Introductionmentioning
confidence: 99%
“…This formalism is inspired by the Induced Matter Theory (IMT), which is based on the assumption that ordinary matter and physical fields that we can observe in our 4D universe can be geometrically induced from a 5D Ricci-flat metric with a space-like noncompact extra dimension on which we define a physical vacuum [10][11][12]. The Campbell-Magaard theorem [13][14][15][16][17] serves as a ladder to move between manifolds whose dimensionality differs by one. This theorem, which is valid in any number of dimensions, implies that every solution of the 4D Einstein equations with arbitrary energy-momentum tensor can be embedded, at least locally, in a solution of the 5D Einstein field equations in vacuum.…”
Section: Introductionmentioning
confidence: 99%